2018
DOI: 10.1002/mp.12824
|View full text |Cite
|
Sign up to set email alerts
|

Image guidance doses delivered during radiotherapy: Quantification, management, and reduction: Report of the AAPM Therapy Physics Committee Task Group 180

Abstract: Balancing ALARA with the requirement for effective target localization requires that imaging dose be managed based on the consideration of weighing risks and benefits to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
0
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 113 publications
(245 reference statements)
6
108
0
7
Order By: Relevance
“…The significant differences in image dose between patient‐1 and patient‐2 or ‐3 are mainly due to the differences in the numbers of image acquisition arcs. By comparing the imaging doses between patient‐2 and patient‐3, it can be seen that the effect of patient size has significant impact on the kV imaging dose with variation in 30%–50% which is constant with the data in literature . Only small effect is observed for MV imaging dose and this is expected as megavoltage beam has larger penetrating power is not affected by patient size significantly.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…The significant differences in image dose between patient‐1 and patient‐2 or ‐3 are mainly due to the differences in the numbers of image acquisition arcs. By comparing the imaging doses between patient‐2 and patient‐3, it can be seen that the effect of patient size has significant impact on the kV imaging dose with variation in 30%–50% which is constant with the data in literature . Only small effect is observed for MV imaging dose and this is expected as megavoltage beam has larger penetrating power is not affected by patient size significantly.…”
Section: Resultssupporting
confidence: 66%
“…As seen in these three patient cases, the additional image dose with optimized LIVE system from kV beam acquisition procedures is clinically insignificant (<2 cGy). Although the imaging dose from MV may be significant, it is still not exceeding the image dose threshold (5% of the prescribed target dose for a typical dose of 8–20 Gy per faction in SBRT) recommended by AAPM TG‐180 . The MV image doses are generally confined to the target area due to limited field opening of the MV imaging beams.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of kV x‐ray imaging beams, it has been demonstrated that accurate dose simulations requires full knowledge of the kV beam energy spectrum . The recently released AAPM TG180 report on image guidance doses delivered during radiotherapy provides a review of some of the literature on the dose delivered by the OBI during treatment. For example, older versions of the Varian OBI (Varian OBI 1.3) can deliver 1–9 cGy to soft tissue and 6–29 cGy to bones from a single cone‐beam CT scan, although lower doses are possible with advanced dose reduction technologies in modern imaging systems.…”
Section: Introductionmentioning
confidence: 99%